STATUS MUTU AIR DI KAWASAN KONSERVASI PERIKANAN (RESERVAT) LEBUNG KARANGAN OGAN ILIR SUMATERA SELATAN - Lisa Novalia; Dade Jubaedah; Arum Setiawan (Universitas Sriwijaya, 2022)
Water conservation areas are also known as fisheries reserves or reserves. Lebung Karangan is a fishery reserve in Ogan Ilir, South Sumatra. Community activities, either directly or indirectly, will produce waste in the form of organic and inorganic waste. This study aims to analyze the water quality status, and to identify the types of pesticides in Lebung Karangan reserve. The study was conducted in the Lebung Karangan reserve, located in Sejaro Sakti Village, Indralaya, Ogan Ilir, South Sumatra, in November 2019. The sampling location was carried out at 4 (four) stations based on considerations of conditions at the research location. Analysis of water quality parameters was carried out in situ and ex situ. The data obtained from water quality measurements were calculated using the Pollution Index (IP) method to determine the status of water quality. The results showed that the water quality status of the Lebung Karangan reserve was in a moderately polluted to heavily pollute state, with an IP value of 10-13,54. The Lebung Karangan reserve was identified as containing organochlorine pesticides. The results of this study are expected to be used as a reference for the government in order to make policies in managing the Lebung Karangan reservae considering the condition of the waters being lightly polluted and the discovery of pesticide compounds. Key words : Lebung Karangan, organochlorine pesticides, reserve, quality status